2017
DOI: 10.1002/pmic.201600433
|View full text |Cite
|
Sign up to set email alerts
|

From Peptide Masses to Pregnancy Maintenance: A Comprehensive Proteomic Analysis of The Early Equine Embryo Secretome, Blastocoel Fluid, and Capsule

Abstract: Early pregnancy in the mare is a poorly understood, high risk period during which the embryo communicates its presence to the maternal endometrium. Remarkably, the maternal recognition of pregnancy signal is unknown in the horse. This study aimed to profile the proteins secreted by equine blastocysts into their immediate environment, along with proteins contained in the blastocoel and within the acellular embryo capsule. Embryos were recovered on day 8 after ovulation and cultured for 48 hours. Secretomes of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 94 publications
5
50
0
Order By: Relevance
“…Similarly, Demetriou et al, [52] suggested a prospective crucial role for this gene in the maintenance of pregnancy in humans. Recently, the importance of the role of FKBP4 protein was showed also in 10-day old horse embryo as it was found within the blastocoel fluid [53]. However, this study could not confirm that this protein was actively secreted into the uterine lumen, or was capable of interaction with the mare's endometrium [53].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, Demetriou et al, [52] suggested a prospective crucial role for this gene in the maintenance of pregnancy in humans. Recently, the importance of the role of FKBP4 protein was showed also in 10-day old horse embryo as it was found within the blastocoel fluid [53]. However, this study could not confirm that this protein was actively secreted into the uterine lumen, or was capable of interaction with the mare's endometrium [53].…”
Section: Discussionmentioning
confidence: 74%
“…Recently, the importance of the role of FKBP4 protein was showed also in 10-day old horse embryo as it was found within the blastocoel fluid [53]. However, this study could not confirm that this protein was actively secreted into the uterine lumen, or was capable of interaction with the mare's endometrium [53]. Although our results showed an up regulation of FKBP4 protein in cyclic heifers, further studies are needed to determine its functions in bovine pregnancy and early embryo development in the oviduct.…”
Section: Discussionmentioning
confidence: 98%
“…Other processes, such as "lipid biosynthetic processes" and "fatty acid metabolic process" were also up-regulated during conceptus development [19]. Comparative proteomics similarly highlighted changes in functional categories of ULF proteins including developmental processes, "binding", response to a stimulus and lipid and cholesterol activity [21,22].…”
Section: Introductionmentioning
confidence: 93%
“…ligand-receptor associations) between the endometrial and conceptus transcriptomes on day 16 [20]. The proteomic profile of day 9 and 10 blastocyst secretions and blastocoele fluid [21], and day 13 uterine luminal (ULF; cyclic and pregnant mares) and yolk sac (blastocoele) fluid have also been reported [22]. The latter studies identified differences in the ULF induced by the presence of a conceptus, and identified proteins secreted by the endometrium or the conceptus into the ULF or yolk sac fluid.…”
Section: Introductionmentioning
confidence: 99%
“…A further study looked for possible relationships (e.g., ligand-receptor associations) between the endometrial and conceptus transcriptomes on day 16 [20]. The proteomic profile of day 9 and 10 blastocyst secretions and blastocoele fluid [21], and day 13 uterine luminal (ULF; cyclic and pregnant mares) and yolk sac (blastocoele) fluid have also been reported [22]. The latter studies identified differences in the ULF induced by the presence of a conceptus, and identified proteins secreted by the endometrium or the conceptus into the ULF or yolk sac fluid.…”
mentioning
confidence: 99%